2016
DOI: 10.14495/jsiaml.8.21
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of multiple precision matrix multiplications using parallelized Strassen and Winograd algorithms

Abstract: It is well known that Strassen and Winograd algorithms can reduce the computational costs associated with dense matrix multiplication. We have already shown that they are also very effective for software-based multiple precision floating-point arithmetic environments such as the MPFR/GMP library. In this paper, we show that we can obtain the same effectiveness for double-double (DD) and quadrupledouble (QD) environments supported by the QD library, and that parallelization can increase the speed of these multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Thus, these algorithms provide better performance when used together with large multiple precision floating-point arithmetic. We confirmed their efficiency through benchmark tests and applications of LU decomposition [ 7 , 8 ].…”
Section: Parallelized Strassen and Winograd Algorithmsmentioning
confidence: 60%
See 1 more Smart Citation
“…Thus, these algorithms provide better performance when used together with large multiple precision floating-point arithmetic. We confirmed their efficiency through benchmark tests and applications of LU decomposition [ 7 , 8 ].…”
Section: Parallelized Strassen and Winograd Algorithmsmentioning
confidence: 60%
“…We have already released multiple precision matrix multiplication library, BNCmatmul [ 10 ] using divide-and-conquer algorithms, including Strassen, and parallelized various precision matrix multiplication based on DD, QD, and MPFR libraries with OpenMP [ 7 , 8 ]. In comparison with Rgemm in MPLAPACK (MBLAS) [ 6 ], it produces better performance for large-sized matrices.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the serial Strassen matrix multiplication and parallelized versions for the large n are more efficient than Rgemm of MP-BLAS [12]. Our accelerated versions of block and Strassen matrix multiplication with AVX2 can be achieved more than two times faster than the MPBLAS for any size of matrices.…”
Section: Computational Time Of Serial Matrix Multiplication and Compa...mentioning
confidence: 89%
“…Among all types of matrix multiplication, we adopted the row-major method to access the elements of matrices and parallelized them by OpenMP [12]. We fixed matrices A and B as follows:…”
Section: Benchmark Tests Of Dd Td and Qd Matrix Multiplicationmentioning
confidence: 99%
“…Kouya et al [14] (second paper) compared parallelized Strassen and Winograd algorithms for multiple precision matrix multiplications using MPFR/GMP and QD libraries. They used thread-based parallelization to improve performance.…”
Section: A Literature Reviewmentioning
confidence: 99%